Effects of diet form and feeder adjustment on growth performance of growing-finishing pigs - Nemechek, J.E.; Fruge, E.; Hansen, E.; Tokach, Michael D.; Goodband, Robert D.; DeRouchey, Joel M.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
A total of 252 pigs (PIC 327 × 1050, initially 125.2 lb BW) were used in a 69-d trial to determine the effects of diet form and feeder adjustment on growth performance of growing-finishing pigs. Treatments were arranged in a 2 × 3 factorial with the main effects of feeder adjustment and diet form. The 2 feeder adjustments were a narrow feeder adjustment (minimum gap opening of 0.50 in.) and a wide adjustment (minimum gap opening of 1.00 in.). The feeders were adjusted to the minimum gap setting, but the agitation plate could be moved upward to a maximum gap opening of 0.75 or 1.25 in. for the narrow and wide adjustments, respectively. The 3 diet forms were meal, poor-quality pellets (50% pellets and 50% fines), and screened pellets with minimal fines. Average daily gain, ADFI, and F/G were determined by weighing pigs and measuring feed disappearance on d 0, 12, 22, 39, 48, and 69. No diet form × feeder adjustment interactions were observed (P > 0.24). For Phases 1 (d 0 to 22) and 2 (d 22 to 48), feeder adjustment did not influence (P > 0.28) ADG, but ADFI tended to increase (P < 0.07) and F/G worsened (P < 0.05) for pigs fed from the wide adjusted feeders. In Phase 3 (d 48 to 69), no differences were detected in growth performance (P > 0.17) between pigs fed from either feeder adjustment.
Keywords: Swine; Diet form; Feeder adjustment; Pellet; Finishing pig